Implementasi Manajemen Produksi pada Pengrajin Batu Bata - Didik Budiyanto; K Budi Hastono; Sandra Oktavina Pinaraswati (Jurnal ABM Mengabdi, 2018)
One of the leading villages in Mojokerto Regency is Karangasem Village with the commodity of Bricks. Currently brick makers face several problems in developing their businesses, among them are: production, marketing, training education and financial governance. The method used is a direct approach to community involvement, an approach to utilizing appropriate technology, an approach that is appealing and support without the element of coercion and socialization and training approaches. The results of the implementation in the field showed improvement in the cleanliness of the environment, arrangement of facilities and infrastructure proved to improve the quality and quantity of production, arrangement and arrangement of scheduling the purchase of raw materials, production and combustion processes greatly determine the readiness of the market to meet market demand. . The availability of coal, sales agents, transport partners along with rising and unloading power and product user partners such as housing greatly determine the sustainability and success of the business.